Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please can you explain me why

$$ \nabla^2 G_{\omega}(R) = f(R) $$

is equivalent to

$$ \frac{1}{R} \frac{d^2(RG_\omega(R))}{d R^2} = f(R) $$


  • $G_\omega(R)$ is the Fourier transform of $G$
  • $G$ is the Green's function
  • We suppose that $G$ and $f$ are spherically symmetric
  • $R = \sqrt{x^2 + y^2 + z^2}$


share|cite|improve this question
up vote 3 down vote accepted

If $H(R)$ is spherically symmetric, we can write the Laplacian of $H$ in spherical coordinates:

$\nabla^2 H = \frac{1}{R^2}\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg)$

(see wikipedia).

Then, $\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg) = R^2\frac{d^2H}{dR^2} + 2R \frac{dH}{dR}$

On the other way, $\frac{d}{dR}(RH(R)) = R\frac{dH}{dR} + H$ and thus

$\frac{d^2}{dR^2}(RH(R)) = R\frac{d^2H}{dR^2} + 2\frac{dH}{dR}$

$\Rightarrow \frac{1}{R^2}\frac{d}{dR}\bigg(R\frac{dH(R)}{dR}\bigg) = \frac{1}{R}\frac{d^2}{dR^2}(RH(R))$

$\Rightarrow \nabla^2 H = \frac{1}{R^2}\frac{d}{dR}\bigg(R^2\frac{dH(R)}{dR}\bigg) = \frac{1}{R}\frac{d^2}{dR^2}(RH(R))$.

Now, apply it to $G_{\omega}$.

share|cite|improve this answer
Thank you very much! – Abramo Oct 29 '10 at 13:36

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.